Transcriptomic Analysis of STAT1/3 in the Goat Endometrium During Embryo Implantation - Liu, Haokun; Wang, Caixia; Li, Zuhui; Shang, Chunmei; Zhang, Xinyan; Zhang, Ruixue; Wang, Aihua; Jin, Yaping; Lin, Pengfei (Frontiers in Veterinary Science, 2021)
Interferon tau (IFNT), a pregnancy recognition signal in ruminants, promotes the establishment of embryo implantation by inducing the expression of interferon-stimulated genes (ISGs) via the Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway. However, the precise regulatory mechanism of IFNT in goat embryo implantation remains largely unknown. In this study, we performed RNA sequencing of goat endometrial epithelial cells (gEECs) with or without 20 ng/mL IFNT treatment. Differential comparison showed that there were 442 upregulated differentially expressed genes (DEGs) and 510 downregulated DEGs. Bioinformatic analyses revealed that DEGs were significantly enriched in immune-related functions or pathways. The qRT-PCR validation results showed that the expression levels of STAT family members (STAT1, STAT2, and STAT3) were significantly upregulated in gEECs after IFNT treatment, which is in agreement with the RNA-seq data. Meanwhile, the protein levels of p-STAT1 and p-STAT3 increased significantly in gEECs after 6 and 24 h of IFNT treatment, respectively. Further in vivo experiments confirmed that both mRNA and protein phosphorylation levels of STAT1 and STAT3 in the uterus on day 18 of pregnancy (P18) were significantly increased compared to those on day 5 (P5) and day 15 of pregnancy (P15). On P5, STAT1 and STAT3 proteins were primarily located in the uterine luminal epithelium (LE) and glandular epithelium (GE) and were also detected in the stromal cells. The intense immunostaining of STAT1 and STAT3 proteins decreased on P15 and then increased on P18, especially in the superficial GE and subepithelial stromal cells. Moreover, p-STAT1 and p-STAT3 were highly expressed in the deep GE on P18. Collectively, these results highlight the role of IFNT in regulating endometrial receptivity in gEECs and uncover the temporal and spatial changes in the expression of STAT1/3 during embryo implantation in the goat endometrium.